Neisseria meningitidis-Induced Caspase-1 Activation in Human Innate Immune Cells Is LOS-Dependent. (6th May 2019) - Idosa, Berhane Asfaw; Kelly, Anne; Jacobsson, Susanne; Demirel, Isak; Fredlund, Hans; Särndahl, Eva; Persson, Alexander
Abstract : Meningococcal disease such as sepsis and meningitidis is hallmarked by an excessive inflammatory response. The causative agent, Neisseria meningitidis, expresses the endotoxin lipooligosaccharide (LOS) that is responsible for activation of immune cells and the release of proinflammatory cytokines. One of the most potent proinflammatory cytokines, interleukin-1 β (IL-1 β ), is activated following caspase-1 activity in the intracellular multiprotein complex called inflammasome. Inflammasomes are activated by a number of microbial factors as well as danger molecules by a two-step mechanism—priming and licensing of inflammasome activation—but there are no data available regarding a role for inflammasome activation in meningococcal disease. The aim of this study was to investigate if N. meningitidis activates the inflammasome and, if so, the role of bacterial LOS in this activation. Cells were subjected to N. meningitidis, both wild-type (FAM20) and its LOS-deficient mutant ( lpxA ), and priming as well as licensing of inflammasome activation was investigated. The wild-type LOS-expressing parental FAM20 serogroup C N. meningitidis (FAM20) strain significantly enhanced the caspase-1 activity in human neutrophils and monocytes, whereas lpxA was unable to induce caspase-1 activity as well as to induce IL-1 β release. While the lpxA mutant induced a priming response, measured as increased expression of NLRP3 and IL1B, the LOS-expressing FAM20 further increased this priming. We conclude that although non-LOS components of N. meningitidis contribute to the priming of the inflammasome activity, LOS per se is to be considered as the central component of N. meningitidis virulence, responsible for both priming and licensing of inflammasome activation.